1983
DOI: 10.2135/cropsci1983.0011183x002300010021x
|View full text |Cite
|
Sign up to set email alerts
|

Trichomes in Segregating Generations of Sorghum Matings. II. Association with Shootfly Resistance1

Abstract: The shootfly (Atherigona soceata Rond.) is a major seedling pest of sorghum in Asia and Africa. To determine whether the presence of nonglandular trichomes on the leaf lamina was associated with resistance to shootfly, trichomed, segregating, and trichomeless F2-derived lines in the F5 and F, from four trlchomed X trichomeless sorghum matings and their parents were studied at ICRISAT Center, Patancheru, India. Trichomed lines had significantly lower percentages of plants with shootfly eggs 18 days after emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This revealed that trichomes on the lower surface is very important and reduces the oviposition. This was in accordance with Blum (1968), Annonymous (1978), Gibson and Maiti (1983) and Maiti and Gibson (1983). On contrary, parent IS 2205 recorded less number of trichomes on the lower surface of the leaf lamina and had much lower numbers of eggs and dead heart per cent than SPSFPR 94004A.…”
Section: Discussionsupporting
confidence: 82%
“…This revealed that trichomes on the lower surface is very important and reduces the oviposition. This was in accordance with Blum (1968), Annonymous (1978), Gibson and Maiti (1983) and Maiti and Gibson (1983). On contrary, parent IS 2205 recorded less number of trichomes on the lower surface of the leaf lamina and had much lower numbers of eggs and dead heart per cent than SPSFPR 94004A.…”
Section: Discussionsupporting
confidence: 82%
“…Genotypes with glossy and trichomed leaves are relatively less susceptible to shoot fly damage (Maiti and Gibson 1983; Sharma and Nwanze 1997; Dhillon et al. 2005, 2006b), while leaf surface wetness is associated with susceptibility to shoot fly in sorghum (Nwanze et al.…”
Section: Discussionmentioning
confidence: 99%
“…The shoot flyresistant genotypes produce more numbers of uniform productive tillers than the susceptible ones, and yield more under shoot fly infestation (Sharma and Nwanze 1997). Genotypes with glossy and trichomed leaves are relatively less susceptible to shoot fly damage (Maiti and Gibson 1983;Sharma and Nwanze 1997;Dhillon et al 2005Dhillon et al , 2006b, while leaf surface wetness is associated with susceptibility to shoot fly in sorghum Dhillon et al 2005). The plumule and leaf sheaths of the shoot fly-resistant genotypes have deeper pink pigment, while the susceptible genotypes were green coloured (Dhillon et al 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes ICSB 425, IS 2312, IS 18662, RSV 1090, RSV 1093, and IS 18551 also showed moderate levels of recovery resistance following shoot fly damage. Oviposition non-preference (antixenosis), antibiosis, and tolerance are the major components of resistance in sorghum to shoot fly (Doggett et al 1970, Raina et al 1981, Sharma and Nwanze 1997, Dhillon et al 2005, 2006a, Kumar et al 2008, and the genotypes having glossy and trichomed leaves are relatively less susceptible to shoot fly damage (Maiti and Bidinger 1979, Maiti and Gibson 1983, Sharma and Nwanze 1997, Dhillon et al 2005, 2006b).…”
Section: Discussionmentioning
confidence: 99%